Health information needs and dissemination methods for individuals living with ischemic heart disease: A systematic review. (March 2023) - Wang, Laureen Y.T.; Lua, Joanne Y.H.; Chan, Cassandra X.C.; Ong, Rachel L.L.; Wee, Caitlin F.; Woo, Brigitte F.Y.
Abstract: Objectives: This review aimed to identify the health information needs and preferred approaches to receive health information of individuals with Ischaemic Heart Disease (IHD). Methods: A systematic review was conducted. Relevant literature, published in English (January 2011 to October 2021), was identified across six databases. Guided by Coulter et al.'s framework for developing patient information materials, thematic analysis was performed. The findings were presented in tables and prose. Results: Fifty-nine studies were included. Eleven themes summarised the information needs of individuals with IHD. Each theme was supported with subthemes. Forty-five studies included information on preferred methods of dissemination. Conclusions: Our review has characterised the diverse information needs of individuals living with IHD and dissemination methods for outreach to this population. Such insights inform healthcare providers in formulating patient-centred educational interventions to empower patients to undertake successful behavioural modification. Practice Implications: Patient education should be personalised and delivered according to individuals' risks for IHD and modifiable risk factors. The use of web-based dissemination of patient education has gained popularity among healthcare providers but sub-optimal adherence to these web-based interventions limits behavioural modification. Adding elements of in-person patient education session to complement web-based interventions may be more propitious to effecting behavioural modification. Highlights: Information needs of individuals with IHD differs from those who have had an AMI. Individuals with IHD have diverse information needs. Digitalisation has transformed the dissemination of information to patients. Patient education should be delivered in a contextualised manner.